Purified Mesenchymal Stem Cells Are an Efficient Source for iPS Cell Induction - Niibe, Kunimichi (Public Library of Science, 2011)
BACKGROUND: Induced pluripotent stem (iPS) cells are generated from mouse and human somatic cells by the forced expression of defined transcription factors. Although most somatic cells are capable of acquiring pluripotency with minimal gene transduction, the poor efficiency of cell reprogramming and the uneven quality of iPS cells are still important problems. In particular, the choice of cell type most suitable for inducing high-quality iPS cells remains unclear. METHODOLOGY/PRINCIPAL FINDINGS: Here, we generated iPS cells from PDGFRα(+) Sca-1(+) (PαS) adult mouse mesenchymal stem cells (MSCs) and PDGFRα(−) Sca-1(−) osteo-progenitors (OP cells), and compared the induction efficiency and quality of individual iPS clones. MSCs had a higher reprogramming efficiency compared with OP cells and Tail Tip Fibroblasts (TTFs). The iPS cells induced from MSCs by Oct3/4, Sox2, and Klf4 appeared to be the closest equivalent to ES cells by DNA microarray gene profile and germline-transmission efficiency. CONCLUSIONS/SIGNIFICANCE: Our findings suggest that a purified source of undifferentiated cells from adult tissue can produce high-quality iPS cells. In this context, prospectively enriched MSCs are a promising candidate for the efficient generation of high-quality iPS cells.